Minimum separation between lightning protection system and non-integrated metallic structures - Fallah, Seyedeh Narjes (2014)
In an event of direct lightning strike to a protected building which is integrated with an electrical or electronic system installed on the roof such as roof-top PV system,dangerous sparking may occur between external lightning protection system (LPS) and conductive components of the electrical system. To prevent such side flashes, a minimum separation distance between the metallic components and air termination system is required. Even though, IEC62305-3 Standard provides a formula to specify the necessary separation distance, so far there is no extensive study that has been done to evaluate the suitability of the application of equation to calculate the separation distance,specifically to the safety of electrical systems integrated into the roof top of building. In this study, a new computational method has been developed for calculation of the separation distance between an LPS and metallic components on the roof. In the proposed method which is based on the theoretical background of the IEC62305-3 Standard formula, the break down behavior of the gap geometry between the LPS and metallic components for the applied voltage across the gap is analyzed. PSCAD software was used to model the LPS and the lightning strokes. Separation distance has been computed considering the voltage-time area of the induced voltage across the gap as rectangle, triangle and trapezium and the results have been compared with the one considering the voltage-time area of the real voltage wave shape. It has been observed that calculated result for separation distance considering the real voltage wave shape is lower than the results for assumed voltage wave shapes. Finally, the value of separation distance which is obtained by the proposed method has been compared to the value obtained by IEC62305-3 Standard formula. The comparison indicates almost 20% difference between the values of separation distances calculated by the proposed method and IEC62305-3 standard formula, whereas the proposed method suggests lower values for separation distance. Therefore, it has been concluded that the IEC62305-3 Standard suggested formula overestimate the values of separation distance. Furthermore, effects of two parameters of resistance and inductance of earthing system that influence the value of separation distance have been investigated. It has been observed that the inductance of the earthing system plays an important role in increasing the potential across the gap and the separation distance in case of fast front lightning current, i.e. subsequent negative stroke and first negative stroke. While, influence of the earth resistance on the value of the separation distance is not remarkable for fast front lightning currents. However, for slow front lightning current such as positive stroke, the earth resistance plays an important role in determining the separation distance.